Determine all functions $f:\mathbb{R}\rightarrow\mathbb{R}$ such that $$(x-2)f(y)+f\big(y+2f(x)\big)=f\big(x+yf(x)\big)$$ for all $x,y\in\mathbb{R}$.

Source: Math Excalibur Volume 22, Number 1 Problem 522

(Functional equations are on-topic, there are few previous functional equations by other users.)

  • 4
    $\begingroup$ To the close voter: yeah nah, this is in no way shape or form a textbook maths problem as opposed to maths puzzle. $\endgroup$ Jun 3, 2020 at 7:45

1 Answer 1


All such function(s) is(are):

$f\equiv 0$ and $f(x)=x-1$. These can be easily seen to work via some algebra.

How so?

Suppose $f(0)=0$ at first. Putting $x=0$ gives $-2f(y)+f(y)=0$, so $f(y)=0$ for all $y$, i.e., $f$ is the all-zero function.

The other case is

when $f(0)\ne 0$. Now plugging $y=0$ gives $(x-2)f(0)=-f(2f(x))+f(x)$. Note that if $f(x_1)=f(x_2)$, then $-f(2f(x_1))+f(x_1)=-f(2f(x_2))+f(x_2)$, so the last relation implies $(x_1-2)f(0)=(x_2-2)f(0)$, so $x_1=x_2$. This means $f$ is injective.

Next, plug in

$x=2$ and $y=0$, to get $f(2f(2))=f(2)\implies 2f(2)=2$ (because of injectivity). Thus $f(2)=1$, and by injectivity, $2$ is the only number whose image is $1$.

We will derive one last thing before the finale.

We claim that the only possible preimage of $0$ is $1$. Indeed, if $f(c)=0$, then putting $y=2,x=c$ gives $(c-2)\cdot 1+1=0$, which gives $c=1$.

Now for the finish. We plug in

$y=\frac{2f(x)-x}{f(x)-1}$ (for $x\ne 2$). Note that this magical substitution makes $f(y+2f(x))$ and $f(x+yf(x))$ cancel out, so we are left with (using $x\ne 2$)$$(x-2)f\left(\frac{2f(x)-x}{f(x)-1}\right)=0\implies f\left(\frac{2f(x)-x}{f(x)-1}\right)=0.$$But by the last inference, this must mean $\frac{2f(x)-x}{f(x)-1}=1$, which can be rearranged to $f(x)=x-1$. We derived this assuming $x\ne 2$, but this is true for $x=2$ as well, so in fact $f(x)=x-1$ has to hold for all $x$.

  • 2
    $\begingroup$ Correct! Quite fast! BTW, someone voted close for my latest two questions! $\endgroup$ Jun 3, 2020 at 5:30
  • 1
    $\begingroup$ Typo at the last sentence, it should be "We derived this assuming $x\neq2$" $\endgroup$
    – justhalf
    Jun 3, 2020 at 10:56
  • $\begingroup$ @justhalf nice catch, fixed! $\endgroup$
    – Ankoganit
    Jun 3, 2020 at 11:51

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.